2005
DOI: 10.1167/iovs.04-1383
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Visual Acuity and Central Retinal Thickness in Retinitis Pigmentosa

Abstract: Both retinal thinning (due to cell loss) and retinal thickening (due to presumed edema) appear to be associated with lower visual acuity in patients with typical retinitis pigmentosa. The definition of the OCT third high-reflectance band may help to predict which patients are more likely to lose visual acuity as retinal thickness declines. An increase or decrease in retinal thickness of more than 17 microm at fixation or 11 microm over the central 1 mm at follow-up can be considered a significant (P < 0.01) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
170
3
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(194 citation statements)
references
References 8 publications
18
170
3
3
Order By: Relevance
“…27 We also showed in an earlier study that the shortening or disappearance of IS/OS was associated with the deterioration of visual acuity and the amplitude of the focal macular electroretinogram. 28 In this study, the status of IS/OS was correlated with visual acuity similar to that seen for the cases without CME.…”
Section: Discussionsupporting
confidence: 55%
“…27 We also showed in an earlier study that the shortening or disappearance of IS/OS was associated with the deterioration of visual acuity and the amplitude of the focal macular electroretinogram. 28 In this study, the status of IS/OS was correlated with visual acuity similar to that seen for the cases without CME.…”
Section: Discussionsupporting
confidence: 55%
“…It has been reported that a foveal thinning measured with the OCT was correlated with the visual acuity in patients with RP and Stargarrt's disease. 11,12,15 Witkin et al 11 reported that the foveal thinning might be primarily due to photoreceptor loss. In our RP patients, Grade 2 eyes had a fovea as thick as that of eyes in Grade 3, and we assumed that the damage of the photoreceptor in Grade 2 eyes was partial, and that the length of the outer segments was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…14 The appearance of the IS/OS in the OCT images at the fovea was graded from 1 to 3: Grade 1, IS/OS not visible; Grade 2, abnormal IS/OS ( Figure 1); and Grade 3, normal IS/OS ( Figure 2). 12 To grade the cases, we measured the length of the IS/OS, which extended from just beneath the fovea, and defined eyes as Grade 3 when the length of the continuous IS/OS line was 40.5 mm. The eyes with disruptions of the IS/OS just beneath the fovea were placed in Grade 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Distortion, shortening, or absence of IS/OS may indicate pathologic changes in photoreceptors as shown in RP 16 as well as in macular hole, 20 retinal detachment, 14 retinal vein occlusion, 21 central serous chorioretinopathy, 13,15,22 or multiple evanescent white dot syndrome. 23 Also in our patients, complete disappearance of IS/OS detected by OCT was correlated with decrease in VA, as expected.…”
Section: Discussionmentioning
confidence: 99%